Os contextos do ensino de teatro na rede pública municipal de João Pessoa - Santos, Claudete Gomes dos (2016)
This field study was carried out by the Master of Arts program in National NetworkPROFARTES, in UFPB, with the aim of investigating the conditions for the development of teaching Theater taught by teachers of the permanent staff in performing arts and/or theatre, in Municipal public schools of João Pessoa. The data were collected through the application of semi-structured interviews with all educators who submitted proof of tender open procedure for the city of João Pessoa, in the years 2007 (for performing arts) and 2013 (for theater), and were teaching in regular classroom of elementary school, during the months of July and August of the year of 2015, so , enabling a withdrawal in the form of a census and subsidizing a quantitativa analysis, primarily, qualitative of reality. Throughout of the dissertation, are described 4 chapters: 1-preliminary thoughts about what is art, culture and knowledge within the school universe, which features some introductory concepts, as well as a brief historical excursus of art education regulatory milestones, as well as describe the rationale and the objectives proposed for this field study; 2-production, which displays the data in the process of developing research, providing elements that reflect the choices of the methodology adopted and paths, then the difficulties and restructuring of the project as a whole; 3-Ladies and gentlemen, that exposes, analytically, the data collected; and 4-post-production, which talks about the considerations identified by the analysis of the recorded data. Thus, through this field study, It is stated the hypothesis that there is a discrepancy between the reality found in the municipal schools of the paraibana capital, with respect to the development of the teaching of art in question, and the norms established by the regulatory educational bodies of Arts (LDB,DCNEF9, PCN and resolutions). So, before the difficulties encountered to teach only theater, most (70%) of the respondents teaching classes with one or more sub-area of the teaching of art for which have not been enabled, namely, polyvalent form. By presenting "the contexts of teaching drama at the Municipal Public Network of João Pessoa", exposes paradigms that demonstrate urgency in the search for alternatives and actions, not only governmental and legal, but, too, of the teachers, for, in fact, hold discussions with the actual needs of school units and, in particular, support the demands of students, within a perspective of education offering focused on the integral formation of citizens.